2011
DOI: 10.1037/a0024635
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of parental attachment bonds to college student development and adjustment: A meta-analytic review.

Abstract: We report findings from a meta-analysis of 156 studies conducted between 1987 and 2009 (N = 32,969) that examined the relationship between self-reported parental attachment and multiple adjustment outcomes and developmental advances during the college years. Overall, a small-to-medium relationship was found between indicators of parental attachment quality and favorable adjustment outcomes (r = .23). Effect sizes were of similar magnitude for mother and father attachment relationships, for male and female stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 150 publications
10
110
2
2
Order By: Relevance
“…Application of Bowlby's (1988) developmental theory of attachment to the study of college student development has challenged the separation-individuation model, as attachment theory postulates that a secure connection to parents is conducive to promoting autonomy across the lifespan. Findings from this work indicate that secure attachment relationships between students and parents enable students' confidence to explore the college environment and offer support during stressful times (Mattanah et al 2011;Sorokou and Weissbrod 2005).…”
Section: Higher Education Literature On Parental Involvementmentioning
confidence: 92%
“…Application of Bowlby's (1988) developmental theory of attachment to the study of college student development has challenged the separation-individuation model, as attachment theory postulates that a secure connection to parents is conducive to promoting autonomy across the lifespan. Findings from this work indicate that secure attachment relationships between students and parents enable students' confidence to explore the college environment and offer support during stressful times (Mattanah et al 2011;Sorokou and Weissbrod 2005).…”
Section: Higher Education Literature On Parental Involvementmentioning
confidence: 92%
“…Several studies examining school adjustment have proved that internal factors, such as individual characteristics (e.g., intelligence and emotional quotients, personality) (Ahammed et al, 2011;Warbah et al, 2007), and external factors, such as perceived stress (e.g., academic stress) (Akgun and Ciarrochi, 2003), relationships (e.g., peers) (Iwata et al, 2014) and home environment (family income and parental conflicts) (Lucas- Thompson and Hostinar, 2013;Nelson et al, 1993) have contributed to the adjustment of college students. A meta-analysis by Mattanah et al (2011) indicated that parental attachment was associated with adjustment outcomes. And these lines of evidence strongly imply that internal and external environments are important factors influencing school adjustment.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore the university context involves a range of unique stressors including: increased study load, academic pressures (i.e., pressure to achieve good grades and graduate), studying in a more self-directed manner, and learning in an environment that is largely unfamiliar (Chemers, Hu & Garcia, 2001;Jones & Frydenberg, 1998). Students are often also juggling the broader developmental tasks and responsibilities associated with their age period, such as establishing independence from primary care givers and consolidating a sense of self-identity (Havighurst, 1972;Mattanah, Lopez & Govern, 2011). Given these challenges, commencing university has been found to be a particularly stressful time for students, testing students' coping strategies and overall resilience (Lopez & Gormley, 2002).…”
Section: Abstract Medical Students Mental Health Wellbeingmentioning
confidence: 99%